Bradycardic Episodes of Trigeminocardiac Reflex During Fluoroscopy-Guided Ganglion Gasseri Radiofrequency Ablation in a Trigeminal Neuralgia Patient: A Case Report - Nurdianto, Muhammad Syarif; Mahmud, Mahmud; Sari, Djayanti; Sari, Dhanty Dwita (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2026)
Background: Trigeminocardiac reflex (TCR) is a known but infrequently reported complication of Ganglion Gasseri interventions, manifesting as profound bradycardia and hemodynamic instability.Case Illustration: A 55-year-old woman with left-sided trigeminal neuralgia, hypertension, and type 2 diabetes underwent fluoroscopy-guided Ganglion Gasseri block with radiofrequency ablation. At the 25th minute of needle manipulation, her heart rate dropped acutely to <30 bpm, followed by a second episode to 30–35 bpm ten minutes later. Both episodes were successfully managed by immediate cessation of manipulation and deepening of sedation using intravenous midazolam (2 mg) and propofol (20 mg), without the need for atropine. Post-procedural pain scores decreased from 7–8 to 2–3 on the Numeric Rating Scale.Conclusion: This case highlights the necessity of vigilant hemodynamic monitoring and the potential role of adequate sedation depth in mitigating vagal responses during trigeminal procedures, particularly in patients with pharmacologically altered autonomic tone